Cerebral metabolic rate of oxygen in obstructive sleep apnea at rest and in response to breath-hold challenge. Issue 4 (April 2016) - Rodgers, Zachary B; Leinwand, Sarah E; Keenan, Brendan T; Kini, Lohith G; Schwab, Richard J; Wehrli, Felix W
Obstructive sleep apnea (OSA) is associated with extensive neurologic comorbidities. It is hypothesized that the repeated nocturnal apneas experienced in patients with OSA may inhibit the normal apneic response, resulting in hypoxic brain injury and subsequent neurologic dysfunction. In this study, we applied the recently developed OxFlow MRI method for rapid quantification of cerebral metabolic rate of oxygen (CMRO2 ) during a volitional apnea paradigm. MRI data were analyzed in 11 OSA subjects and 10 controls (mean ± SD apnea-hypopnea index (AHI): 43.9 ± 18.1 vs. 2.9 ± 1.6 events/hour, P < 0.0001; age: 53.8 ± 8.2 vs. 45.3 ± 8.5 years, P = 0.027; BMI: 36.6 ± 4.4 vs. 31.9 ± 2.2 kg/m 2, P = 0.0064). Although total cerebral blood flow and arteriovenous oxygen difference were not significantly different between apneics and controls ( P > 0.05), apneics displayed reduced baseline CMRO2 (117.4 ± 37.5 vs. 151.6 ± 29.4 µmol/100 g/min, P = 0.013). In response to apnea, CMRO2 decreased more in apneics than controls (−10.9 ± 8.8 % vs. −4.0 ± 6.7 %, P = 0.036). In contrast, group differences in flow-based cerebrovascular reactivity were not significant. Results should be interpreted with caution given the small sample size, and future studies with larger independent samples should examine the observed associations, including potential independent effects of age or BMI. Overall, these data suggest that dysregulation of the apneic response may be a mechanism for OSA-associated neuropathology.